Choice of the Optimal Dialysate Sodium Concentration - Christopher W. McIntyre (MDPI AG, 2022)
The choice of dialysate sodium concentration remains amongst the most crucial and difficult to address challenges, in the care of hemodialysis (HD) patients. Our understanding of the determinants of sodium transport, as well as the consequences of getting the decisions wrong, remains both imperfect and evolving. This question has been subject to far less study than it deserves. In this short piece we consider what we are trying to achieve with dialysate sodium choices and how best to individualize those choices to address the symptomatic and survival-based needs of our patients.